Predicting Pediatricians’ Communication With Parents About the Human Papillomavirus (HPV) Vaccine: An Application of the Theory of Reasoned Action - Roberto, Anthony J. (2011)
This study examines the ability of the theory of reasoned action (TRA) and the theory of planned behavior (TPB) to predict whether or not pediatricians encourage parents to get their adolescent daughters vaccinated against the human papillomavirus (HPV). Four-hundred and six pediatricians completed a mail survey measuring attitudes, subjective norms, perceived behavioral control, intentions, and behavior. Results indicate that pediatricians have positive attitudes, subjective norms, and perceived behavioral control toward encouraging parents to get their daughters vaccinated, that they intend to regularly encourage parents to get their daughters vaccinated against HPV in the next 30 days, and that they had regularly encouraged parents to get their daughters vaccinated against HPV in the past 30 days (behavior). Though the data were consistent with both the TRA and TPB models, results indicate that perceived behavioral control adds only slightly to the overall predictive power of the TRA, suggesting that attitudes and norms may be more important targets for interventions dealing with this topic and audience. No gender differences were observed for any of the individual variables or the overall fit of either model. These findings have important theoretical and practical implications for the development of health communication messages targeting health care providers in general, and for those designed to influence pediatricians’ communication with parents regarding the HPV vaccine in particular.